ANALISIS HUBUNGAN-HUBUNGAN DERMATITIS KONTAK ALERGI PADA PEMULUNG - Wiratama, Rifki; Cahyati, Widya Hary; Laksono, Budi (Universitas Esa Unggul, 2020)
AbstractGlobally dermatitis affects about 230 million people or 3.5% of the world's population. The prevalence is dominated by women, especially in the reproductive period, namely the age of 15-49 years, the prevalence of dermatitis in Indonesia is 6.78%, thus work contact is one of the most frequently reported events and the incidence varies between 50-190 cases per 100,000 workers per year . This study aims to analyze the relationship of personal hygiene, knowledge, the use of self-protection equipment, and the working period of allergic contact dermatitis in scavengers in the Yogyakarta Piyungan landfill. This type of research is observational analytic research with cross sectional design. The research sample was 112 scavengers. The analysis of this research uses Path Analysis. The results showed that there was a direct relationship of personal hygiene to allergic contact dermatitis with path coefficient of 0.243 (p = 0.003 <0.05), there was a direct relationship of knowledge of allergic contact dermatitis with path coefficient of 0.216 (p = 0.000 <0.05), there was the relationship of PPE use to allergic contact dermatitis with path coefficient of 0.124 (p = 0.001 <0.05), there is a relationship of working period to allergic contact dermatitis with path coefficient of 0.253 (p = 0.000 <0.05).Keywords: Allergic contact dermatitis, scavengers, personal hygieneÂ Â Â Â Â Â Â Â Â Â Â Â AbstrakSecara global dermatitis mempengaruhi sekitar 230 juta orang atau 3,5% dari populasi dunia. Prevalensi di dominasi kelompok perempuan khususnya dalam periode reproduksi yaitu umur 15-49 tahun, prevalensi dermatitis di Indonesia sebesar 6,78%, demikian kontak akibat kerja merupakan salah satu kejadian yang sering dilaporkan dan insidennya bervariasi diantara 50-190 kasus per 100.000 pekerja per tahun. Penelitian ini bertujuan untuk menganalisis hubungan personal hygiene, pengetahuan, pemakaian alat pelindug diri, dan masa kerja terhadap dermatitis kontak alergi pada pemulung di tempat pembuangan sampah Piyungan Yogyakarta. Jenis penelitian ini adalah penelitian analitik observasional dengan desain cross sectional. Sampel penelitian adalah 112 pemulung. Analisis penelitian ini menggunakan Path Analysis. Hasil penelitian menunjukkan bahwa ada hubungan langsung daripersonal hygieneÂ terhadap dermatitis kontak alergi dengan koefisen jalur sebesar 0.243 (p=0.003<0.05), ada hubungan langsung daripengetahuan terhadap dermatitis kontak alergi dengan koefisen jalur sebesar 0.216 (p=0.000<0.05), ada hubungan pemakaian APD terhadap dermatitis kontak alergi dengan koefisen jalur sebesar0.124 (p=0.001<0.05), ada hubungan masa kerja terhadap dermatitis kontak alergi dengan koefisen jalur sebesar0.253 (p=0.000<0.05). Kata kunci: Dermatitis kontak alergi, pemulung,personal hygiene